Lithium-ion conductive solid material

JP7636755B2Active Publication Date: 2025-02-27BASF SE +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2022504609
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-24
Filing Date
2020-07-21
Publication Date
2025-02-27
Estimated Expiration
2040-07-21

Smart Images

  • Figure 0007636755000002
    Figure 0007636755000002
  • Figure 0007636755000003
    Figure 0007636755000003
  • Figure 0007636755000001
    Figure 0007636755000001
Patent Text Reader

Abstract

The present invention describes a solid-state material having ionic conductivity for lithium ions, a method for preparing said solid-state material, a method for using said solid-state material as a solid electrolyte for an electrochemical cell, a solid-state structure selected from the group consisting of a cathode, an anode, a separator for an electrochemical cell comprising the solid-state material, and an electrochemical cell comprising such a solid-state structure.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention describes a solid-state material having ionic conductivity for lithium ions, a method for preparing said solid-state material, a method for using said solid-state material as a solid electrolyte for an electrochemical cell, a solid-state structure selected from the group consisting of a cathode, an anode, a separator for an electrochemical cell comprising said solid-state material, and an electrochemical cell comprising such a solid-state structure. [Background technology]

[0002] Solid-state lithium batteries are widely used, which has created a high demand for solid-state electrolytes with high lithium-ion conductivity. An important class of such solid electrolytes is lithium arginite.

[0003] US8,075,865B2 is a compound of the formula ( * ) lithium arginine germanite, Li (12-n-x) B n+ X 2- 6-x Y - x ( * ) During the ceremony, B is selected from the group consisting of P, As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb, and Ta; X is selected from the group consisting of S, Se, and Te; Y is selected from the group consisting of Cl, Br, I, F, CN, OCN, SCN, and N3, with 0≦x≦2. For the specific compound Li6PS5I, about 7 * 10 -3 Ionic conductivities in S / cm are reported in US 8,075,865 B2.

[0004] Marvin A. Kraft et al. (J. Am. Chem. Soc. 2018, 140, 16330-16339) Li 6+x Ge x P 1-xS5I The article discloses lithium arginine ore of where x is 0, 0.15, 0.25, 0.3, and 0.6, respectively. Depending on x and its preparation method, such sintered pellets of lithium argoniogermanite may exhibit ionic conductivities of up to 5.4±0.8 mS / cm, or up to 18.4±2.7 mS / cm.

[0005] There is a continuing need for lithium conductors that exhibit suitable ionic conductivity for use as solid electrolytes in all-solid-state lithium batteries, as well as electrochemical stability in direct contact with lithium metal. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] US8,075,865B2 [Non-patent literature]

[0007] [Non-Patent Document 1] Marvin A. Kraft et al. (J. Am. Chem. Soc. 2018, 140, 16330-16339) Summary of the Invention [Problem to be solved by the invention]

[0008] It is an object of the present disclosure to provide a solid-state material that can be used as a solid electrolyte in an electrochemical cell. Further provided are a method for preparing said solid-state material, a method for using said solid-state material as a solid-state electrolyte for an electrochemical cell, a solid-state structure selected from the group consisting of a cathode, an anode and a separator for an electrochemical cell comprising said solid-state material, and an electrochemical cell having such a solid-state structure, wherein said solid-state structure comprises said solid-state material. [Means for solving the problem]

[0009] According to a first aspect, there is provided a solid material having a composition according to general formula (I): Li 7+x-y M x Sb 1-x S 6-y X y (I) (In the formula, M is one or more selected from the group consisting of Si, Ge, and Sn; 0≦x≦1; X is one or more selected from the group consisting of Cl, Br, and I; 0.05≦y≦2). [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 shows the voltage profile of the solid electrolyte. [Diagram 2] FIG. 2 shows the XRD pattern of a solid material having a composition according to formula (I). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Surprisingly, it has been found that the solid-state materials defined above can exhibit good lithium ion conductivity and electrochemical stability in direct contact with lithium metal.

[0012] A particular material according to the first aspect defined above has a composition according to formula (I) where X is I (iodine), i.e. a composition according to formula (Ia): Li 7+x-y M x Sb 1-x S 6-y I y (Ia) wherein M, x and y have the same meanings as defined above for formula (I).

[0013] The first group of solid materials according to the first aspect defined above has a composition according to formula (I) where x = 0, that is, there is no element M selected from the group consisting of Si, Ge, and Sn. Thus, the solid materials of the first group have a composition according to formula (Ib), Li 7-y SbS 6-y X y (Ib) wherein X and y have the same meanings as defined above for formula (I).

[0014] The specific solid materials of the first group have a composition according to formula (Ib) where 0.5 ≦ y ≦ 1.5, more preferably 0.8 ≦ y ≦ 1.2.

[0015] The specific solid materials of the first group have a composition according to formula (Ib) where X is I.

[0016] The specific solid materials of the first group have a composition according to formula (Ib) where 0.5 ≦ y ≦ 1.5 and X is I. Further specific solid materials of the first group have a composition according to formula (Ib) where 0.8 ≦ y ≦ 1.2 and X is I.

[0017] The second group of solid materials according to the first aspect defined above has a composition according to formula (I) where 0 < x ≦ 1, that is, there is one or more elements M selected from the group consisting of Si, Ge, and Sn.

[0018] The specific solid materials of the second group have a composition according to formula (I) where 0.05 ≦ x ≦ 1.

[0019] The specific solid materials of the second group have a composition according to formula (I) where 0.5 ≦ y ≦ 1.5, preferably 0.8 ≦ y ≦ 1.2.

[0020] The specific solid materials of the second group have a composition according to formula (I) where 0.05 ≦ x ≦ 1, 0.5 ≦ y ≦ 1.5, preferably 0.8 ≦ y ≦ 1.2.

[0021] The second group of specific solid materials has a composition according to formula (I) where X is I.

[0022] The second group of specific solid materials has a composition according to formula (I) with 0.05≦x≦1, 0.5≦y≦1.5, and X is I. A further second group of specific solid materials has a composition according to formula (I) with 0.05≦x≦1, 0.8≦y≦1.2, and X is I.

[0023] A second group of solid state materials in which M is Si has a composition according to formula (Ic): Li 7+x-y S x Sb 1-x S 6-y X y (I C) During the ceremony, 0 <x≦1; X and y have the same meanings as defined above for formula (I).

[0024] Said second group of particular solid state materials in which M is Si has a composition according to formula (Ic), wherein 0.1≦x≦0.8, preferably 0.2≦x≦0.7, even more preferably 0.3≦x≦0.7, and even more preferably 0.4≦x≦0.7.

[0025] Said second group of particular solid state materials in which M is Si has a composition according to formula (Ic) where 0.5≦y≦1.5, preferably 0.8≦y≦1.2, more preferably y is between 0.9 and 1.1.

[0026] The second group of particular solid state materials in which M is Si has a composition according to formula (Ic) wherein 0.1≦x≦0.8, preferably 0.2≦x≦0.7 and 0.5≦y≦1.5, preferably 0.8≦y≦1.2, more preferably 0.2≦x≦0.7 and 0.8≦y≦1.2, even more preferably 0.3≦x≦0.7 and 0.8≦y≦1.2, even more preferably 0.3≦x≦0.7 and 0.9≦y≦1.1, and most preferably 0.4≦x≦0.7 and 0.9≦y≦1.1.

[0027] A particular solid state material of said second group, in which M is Si, has a composition according to formula (Ic), in which X is I.

[0028] The second group of specific solid materials, where M is Si and X is I, has a composition according to formula (Ic), where 0.1≦x≦0.8 and 0.5≦y≦1.5. The second group of further specific solid materials, where M is Si and X is I, has a composition according to formula (Ic), where 0.2≦x≦0.7 and 0.8≦y≦1.2, more preferably 0.3≦x≦0.7 and 0.8≦y≦1.2, even more preferably 0.3≦x≦0.7 and 0.9≦y≦1.1, and most preferably 0.4≦x≦0.7 and 0.9≦y≦1.1.

[0029] A second group of solid state materials in which M is Ge has a composition according to formula (Id): Li 7+x-y Ge x Sb 1-x S 6-y X y (Id) During the ceremony, 0 <x≦1; X and y have the same meanings as defined above for formula (I).

[0030] Particular solid state materials of said second group in which M is Ge have a composition according to formula (Id), with 0.1≦x≦0.5, preferably 0.2≦x≦0.4.

[0031] Said second group of particular solid state materials in which M is Ge has a composition according to formula (Id), where 0.5≦y≦1.5, preferably 0.8≦y≦1.2, more preferably y is between 0.9 and 1.1.

[0032] The second group of particular solid state materials wherein M is Ge has a composition according to formula (Id) wherein 0.1≦x≦0.5, preferably 0.2≦x≦0.4 and 0.5≦y≦1.5, preferably 0.8≦y≦1.2, more preferably 0.2≦x≦0.4 and 0.8≦y≦1.2, and even more preferably 0.2≦x≦0.4 and 0.9≦y≦1.1.

[0033] Particular solid state materials of said second group, in which M is Ge, have a composition according to formula (Id), in which X is I.

[0034] The second group of specific solid state materials, where M is Ge and X is I, has a composition according to formula (Id), where 0.1≦x≦0.5 and 0.5≦y≦1.5. A further second group of specific solid state materials, where M is Ge and X is I, has a composition according to formula (Id), where 0.2≦x≦0.4 and 0.8≦y≦1.2, more preferably 0.2≦x≦0.4 and 0.9≦y≦1.1.

[0035] A second group of solid state materials in which M is Sn has a composition according to formula (Ie): Li 7+x-y Sn x Sb 1-x S 6-y X y (Ie) During the ceremony, 0 <x≦1; X and y have the same meanings as defined above for formula (I).

[0036] Said second group of particular solid state materials in which M is Sn have a composition according to formula (Ie) with 0.1≦x≦0.3, preferably 0.15≦x≦0.25.

[0037] The second group of particular solid state materials where M is Sn has a composition according to formula (Ie) where 0.5≦y≦1.5, preferably 0.8≦y≦1.2, more preferably y is between 0.9 and 1.1.

[0038] The second group of particular solid state materials, where M is Sn, has a composition according to formula (Ie), where 0.1≦x≦0.3, preferably 0.15≦x≦0.25 and 0.5≦y≦1.5, preferably 0.8≦y≦1.2, more preferably 0.15≦x≦0.25 and 0.8≦y≦1.2, even more preferably 0.15≦x≦0.25 and 0.9≦y≦1.1.

[0039] Particular solid state materials of said second group, where M is Sn, have a composition according to formula (Ie), where X is I.

[0040] Certain solid state materials of said second group, where M is Sn and X is I, have a composition according to formula (Ie), where 0.1≦x≦0.3 and 0.5≦y≦1.5. Further specific solid state materials of said second group, where M is Sn and X is I, have a composition according to formula (Ie), where 0.15≦x≦0.25 and 0.8≦y≦1.2, preferably 0.15≦x≦0.25 and 0.9≦y≦1.1.

[0041] The solid material according to the first aspect defined above may be crystalline detectably by X-ray diffraction. A solid material is called crystalline if it exhibits the long-range order characteristic of crystals, as indicated by the presence of well-defined reflections in the X-ray diffraction pattern. In this context, a reflection is considered well-defined if its intensity is more than 10% higher than the background.

[0042] The crystalline solid state material according to the first aspect defined above may have the arginite structure characterised by the cubic space group F-43m.

[0043] The crystalline solid material according to the first aspect defined above may be accompanied by secondary and / or impurity phases having a composition other than according to general formula (I) defined above, in which case the volume fraction of the phases formed from the crystalline solid material having a composition according to general formula (I) may be 50% or more, possibly 80% or more, preferably 90% or more, most preferably 95% or more, based on the total volume of the solid material according to the first aspect defined above and all secondary and impurity phases.

[0044] If present, the secondary and impurity phases are mainly composed of the precursors used to prepare the solid material, e.g. LiX, where X is as defined above, Li2S and possibly impurity phases which may originate from impurities of the precursors. For details of the preparation of the solid material according to the first aspect defined above, please refer to the information provided below in the context of the second aspect of the present disclosure.

[0045] Optionally, the solid material according to the first aspect defined above is in the form of a polycrystalline powder or in the form of a single crystal.

[0046] The solid-state material according to the first aspect defined above may have an ionic conductivity of at least 0.1 mS / cm, preferably at least 1 mS / cm, more preferably at least 10 mS / cm, in each case at a temperature of 25° C. The ionic conductivity is determined in the usual manner known in the field of battery materials development using electrochemical impedance spectroscopy (see the Examples section below for details).

[0047] At the same time, the solid-state material according to the first aspect defined above may have an almost negligible electronic conductivity. More specifically, the electronic conductivity may be at least three orders of magnitude smaller than the ionic conductivity, preferably at least five orders of magnitude smaller than the ionic conductivity. In some cases, the solid-state material according to the first aspect defined above may have a conductivity of at least 10 -9 The electronic conductivity is determined by direct current (DC) polarization measurements at different voltages, using conventional methods known in the field of battery materials development.

[0048] The solid-state material according to the first aspect defined above shows promising electrochemical stability in direct contact with lithium metal for a sustained period of at least 1,000 hours, resulting in a stable voltage profile even at high currents and capacities under conditions of stripping and plating in symmetrical cells (see the Examples section below for details). This is an important advantage, since it may be possible to apply electrochemical cell configurations in which lithium metal is in direct contact with a solid electrolyte in the form of the solid-state material according to the first aspect defined above, such that a protective layer between the lithium metal and the solid electrolyte can be omitted. Thus, the complexity of the configuration and of the method of manufacture of an electrochemical cell comprising metallic lithium as electroactive material is reduced.

[0049] Preferred solid state materials according to the first aspect defined above are those having one or more of the specific characteristics disclosed above.

[0050] According to a second aspect, there is provided a method for obtaining a solid material according to the first aspect defined above, said method comprising the following method steps: a) Precursors of (1) Li2S (2) Sb2S3 and / or element Sb (3) one or more compounds LiX, in which X is selected from the group consisting of Cl, Br and I (4) Element S (5) optionally, one or more species selected from the group consisting of elemental forms of M and sulfides of M, where M in each instance is selected from the group consisting of Si, Ge, and Sn; wherein in said reaction mixture the molar ratios of the elements Li, M, Sb, S and X correspond to general formula (I); b) heat treating the reaction mixture at a temperature range of 400° C. to 600° C. for a total duration of 40 to 200 hours to form a reaction product; c) cooling the reaction product formed in step b) so as to obtain a solid material having a composition according to general formula (I); Includes.

[0051] In step a) of the method according to the second aspect defined above, a reaction mixture is provided comprising a precursor of the reaction product formed in step b), said precursor being (1) Li2S (2) Sb2S3 and / or elemental Sb as a source of antimony (3) one or more compounds LiX, in which X is selected from the group consisting of Cl, Br and I (4) Elemental sulfur (S) (5) optionally one or more species selected from the group consisting of elemental forms of Si, Ge, and Sn, and sulfides of Si, Ge, and Sn; It is.

[0052] In said reaction mixture, the molar ratios of the elements Li, M, Sb, S and X correspond to general formula (I). The reaction mixture provided or prepared in step a) consists of precursors (1) to (4) or precursors (1) to (5), respectively, as defined above.

[0053] Either or both of elemental forms of Sb (antimony) or Sb2S3 (precursor (2)) may serve as the source of Sb for the solid material having a composition according to formula (I) defined above. In either case, additional sulfur (precursor (4)) is required to oxidize elemental Sb (oxidation state 0) and Sb in Sb2S3 (oxidation state +3) to oxidation state +5, respectively. As precursor (2), Sb2S3 is preferred.

[0054] One or more species (precursor (5)) selected from the group consisting of elemental forms of Si, Ge and Sn, and sulfides of Si, Ge and Sn may serve as a source of M (as defined above) in the solid material having a composition according to formula (I) as defined above. If the oxidation state of element M (as defined above) in precursor (5) is lower than +4, additional sulfur (precursor (4)) is required to oxidize element M to oxidation state +4. This is the case when elemental form of M is used as precursor (5). Among the sulfides of M, those in which the oxidation state of M is +4 (MS2) are preferred. When MS2 is used as precursor (5), additional sulfur is not required to oxidize element M to oxidation state +4.

[0055] Thus, the amount of elemental sulfur (precursor (4)) in the reaction mixture provided or prepared in step a) depends on the oxidation state of Sb in precursor (2) and, if present, the oxidation state of M in precursor (5). Based on stoichiometric considerations, the skilled person can easily calculate the amount of elemental sulfur required in the reaction mixture provided or prepared in step a).

[0056] In a particular method according to the second aspect defined above, precursor (3) is LiI. Such a method is suitable for preparing a solid material having a composition according to general formula (Ia) defined above.

[0057] Thus, the precursor of the solid material having the composition according to the general formula (Ia) (1) Li2S (2) one or more of Sb2S3 and element Sb, preferably Sb2S3 (3) LiI (4) Elemental sulfur (S) (5) optionally one or more species selected from the group consisting of elemental forms of Si, Ge, and Sn, and sulfides of Si, Ge, and Sn; It is.

[0058] In a particular method according to the second aspect defined above, the reaction mixture provided or prepared in step a) does not comprise any precursor (5) selected from the group consisting of elemental forms of Si, Ge and Sn, and sulfides of Si, Ge and Sn. Said reaction mixture provided or prepared in step a) may consist of precursors (1) to (4) as defined above. Such a method is suitable for preparing a solid material having a composition according to general formula (Ib) as defined above. In a particular method for preparing a solid material having a composition according to general formula (Ib), precursor (3) is LiI.

[0059] Thus, the precursor of the solid material having a composition according to general formula (Ib) (1) Li2S (2) one or more of Sb2S3 and element Sb, preferably Sb2S3 (3) one or more compounds LiX, preferably LiI, where X is selected from the group consisting of Cl, Br and I (4) Elemental sulfur (S) It is.

[0060] In a particular method according to the second aspect defined above, the reaction mixture provided or prepared in step a) comprises one or more precursors (5) selected from the group consisting of Si, Ge and Sn in elemental form and sulfides of Si, Ge and Sn. Said reaction mixture provided or prepared in step a) can consist of precursors (1) to (5) as defined above. Such a method is suitable for preparing solid materials of the second group defined above. In a particular method for preparing such solid materials, precursor (3) is LiI.

[0061] Thus, in a particular method according to the second aspect defined above, the precursor comprises (1) Li2S, (2) Sb2S3 or element Sb, (3) LiI, (4) element S and (5) One of the elements Si, Ge, Sn, SiS2, GeS2, and SnS2 It is.

[0062] In a particular method according to the second aspect defined above, the reaction mixture provided or prepared in step a) comprises one or more precursors (5) selected from the group consisting of elemental Si and sulfides of Si. Said reaction mixture provided or prepared in step a) may consist of precursor (5) in the form of one or more species selected from the group consisting of precursors (1) to (4) as defined above and elemental Si and sulfides of Si. Among the sulfides of Si, SiS2 is preferred. Elemental Si (silicon) is preferred as precursor (5). Such a method is suitable for preparing a solid material having a composition according to general formula (Ic) defined above. In a particular method for preparing a solid material having a composition according to general formula (Ic), precursor (3) is LiI.

[0063] Thus, the precursor of the solid material having the composition according to the general formula (Ic) (1) Li2S (2) one or more of Sb2S3 and element Sb, preferably Sb2S3 (3) one or more compounds LiX, preferably LiI, where X is selected from the group consisting of Cl, Br and I (4) Elemental sulfur (S) (5) one or more species selected from the group consisting of Si and sulfides of Si, preferably element Si It is.

[0064] In a particular method according to the second aspect defined above, the reaction mixture provided or prepared in step a) comprises one or more precursors (5) selected from the group consisting of element Ge (germanium) and sulfides of Ge. Said reaction mixture provided or prepared in step a) may consist of precursor (5) in the form of one or more species selected from the group consisting of precursors (1) to (4) as defined above and sulfides of element Ge and Ge. Among the sulfides of Ge, GeS2 is preferred. GeS2 is preferred as precursor (5). Such a method is suitable for preparing a solid material having a composition according to general formula (Id) defined above. In a particular method for preparing a solid material having a composition according to general formula (Id), precursor (3) is LiI.

[0065] Thus, the precursor of the solid material having a composition according to general formula (Id) can be (1) Li2S (2) one or more of Sb2S3 and element Sb, preferably Sb2S3 (3) one or more compounds LiX, preferably LiI, where X is selected from the group consisting of Cl, Br and I (4) Elemental sulfur (S) (5) one or more species selected from the group consisting of the elements Ge and sulfides of Ge, preferably GeS2 It is.

[0066] In a particular method according to the second aspect defined above, the reaction mixture provided or prepared in step a) comprises one or more precursors (5) selected from the group consisting of the element Sn (tin) and sulfides of Sn. Said reaction mixture provided or prepared in step a) may consist of precursors (1) to (4) as defined above and precursor (5) in the form of one or more species selected from the group consisting of the element Sn and sulfides of Sn. Among the sulfides of Sn, SnS2 is preferred. SnS2 is preferred as precursor (5). Such a method is suitable for preparing a solid material having a composition according to the general formula (Ie) defined above. In a particular method for preparing a solid material having a composition according to the general formula (Ie), precursor (3) is LiI.

[0067] Thus, the precursor of the solid material having a composition according to general formula (Ie) is (1) Li2S (2) one or more of Sb2S3 and element Sb, preferably Sb2S3 (3) one or more compounds LiX, preferably LiI, where X is selected from the group consisting of Cl, Br and I (4) Elemental sulfur (S) (5) One or more species selected from the group consisting of elemental Sn and sulfides of Sn, preferably SnS2 It is.

[0068] In step a), the mixing may be carried out by grinding. Grinding may be carried out using any suitable means.

[0069] In step a), it is useful for any treatment to take place under a protective gas atmosphere.

[0070] The reaction mixture prepared or provided in step a) may be formed into pellets, which are heat treated in step b), after which a solid material in the form of pellets or chunks is obtained, which may be ground into a powder for further processing.

[0071] In step b) of the process according to the second aspect defined above, the reaction mixture prepared in process step a) is thermally treated to allow reaction of the precursors, said reaction being considered as a substantially solid-state reaction, i.e. taking place in the reaction mixture in the solid state.

[0072] The heat treatment can be carried out in a closed vessel, which can be a sealed quartz tube or any other type of vessel, such as a vitreous carbon crucible or a tantalum crucible, that can withstand the temperatures of the heat treatment and does not react with any of the precursors.

[0073] Step b) may comprise two or more heat treatment stages, in each stage a different temperature is applied, in the range of 400°C to 600°C, preferably 450°C to 550°C. Generally, in the second stage and each subsequent stage the temperature of the heat treatment is lower than the previous stage. The duration of said stages may be the same or different, the total duration of the heat treatment in the temperature range of 400°C to 600°C being of duration between 40 hours and 200 hours.

[0074] Heating of the reaction mixture to the desired temperature is preferably carried out using a heating rate of 1-10° C. per minute. If the temperature is changed during step b), the temperature change rate is preferably 1-10° C. per minute.

[0075] In a particular method for preparing a material having a composition according to formula (Ic), the heat treatment is carried out at a temperature ranging from 450° C. to 600° C., preferably from 500° C. to 550° C., for a duration of 6 to 8 days.

[0076] In a particular method for preparing a material having a composition according to formula (Id), the heat treatment is carried out in a first stage having a duration of 10 to 30 hours at a temperature in the range of 500°C to 600°C, preferably 500°C to 550°C, followed by a second stage having a duration of 80 to 120 hours at a temperature in the range of 400°C to 500°C, preferably 400°C to 450°C, during which the temperature is lower than during the first stage.

[0077] In a particular method for preparing a material having a composition according to formula (Ie), the heat treatment is carried out at a temperature ranging from 400° C. to 600° C., preferably from 500° C. to 550° C., for a duration of 40 to 60 hours.

[0078] Once the duration of the heat treatment of step b) is complete, the reaction product formed is cooled (step c), thus obtaining a solid material having a composition according to general formula (I).

[0079] The reaction product is preferably cooled at a cooling rate of 1 to 10° C. per minute.

[0080] A preferred method according to the second aspect defined above comprises the following steps: d) annealing the solid material obtained in step c) at a temperature ranging from 400° C. to 600° C. for a duration ranging from 40 hours to 200 hours; Further includes:

[0081] The solid material obtained in step c) may be crushed and formed into pellets and annealed in step d), after which the annealed material is obtained in the form of pellets or chunks, which can be crushed into powder for further processing.

[0082] The annealing (step d)) serves to repair structural defects in the solid material obtained in step c) and / or to fuse the material grains of the solid material obtained in step c).

[0083] The preferred temperature and time ranges, heating rates, and equipment for step d) are similar to those disclosed above for process step b).

[0084] Once the annealing time of step d) is completed, the annealed material is cooled.

[0085] The annealing treatment (step d) was found to result in an increase in the ionic conductivity of the resulting material.

[0086] Preferred methods according to the second aspect defined above are those having one or more of the particular features disclosed above.

[0087] The solid-state material according to the first aspect defined above, respectively obtainable by the method according to the second aspect defined above, can be used as a solid electrolyte for an electrochemical cell, where the solid electrolyte can form a component of a solid structure for an electrochemical cell, said solid structure being selected from the group consisting of a cathode, an anode and a separator. Thus, the solid-state material according to the first aspect defined above, respectively obtainable by the method according to the second aspect defined above, can be used, alone or in combination with additional components, to manufacture a solid structure of an electrochemical cell, such as a cathode, an anode or a separator.

[0088] The present disclosure therefore further provides the use of a solid-state material according to the first aspect defined above, respectively obtainable by a method according to the second aspect defined above, as a solid electrolyte for an electrochemical cell. More specifically, the present disclosure further provides the use of a solid-state material according to the first aspect defined above, respectively obtainable by a method according to the second aspect defined above, as a component of a solid structure for an electrochemical cell, wherein said solid structure is selected from the group consisting of a cathode, an anode and a separator.

[0089] In the context of this disclosure, an electrode that develops a net negative charge during discharge is referred to as the anode, and an electrode that develops a net positive charge during discharge is referred to as the cathode. A separator electrically separates the cathode and anode from each other within the electrochemical cell.

[0090] The cathode of an all-solid-state electrochemical cell typically comprises a solid electrolyte as an additional component in addition to the active cathode material, and the anode of an all-solid-state electrochemical cell typically comprises a solid electrolyte as an additional component in addition to the active anode material.

[0091] The morphology of the solid-state structures of electrochemical cells, particularly all-solid-state lithium batteries, depends in particular on the morphology of the electrochemical cell itself to be produced.

[0092] The present disclosure further provides a solid structure for an electrochemical cell, the solid structure being selected from the group consisting of a cathode, an anode and a separator, the solid structure for an electrochemical cell comprising a solid material according to the first aspect defined above, respectively obtained by a method according to the second aspect defined above. More specifically, there is provided a solid structure as defined above, in which the solid material according to the first aspect defined above, respectively obtained by a method according to the second aspect defined above, is in direct contact with lithium metal.

[0093] The present disclosure further provides an electrochemical cell comprising a solid-state material according to the first aspect defined above, respectively obtainable by a method according to the second aspect defined above, in which the solid-state material according to the first aspect defined above, respectively obtainable by a method according to the second aspect defined above, may form a component of one or more solid structures selected from the group consisting of a cathode, an anode and a separator. More specifically, in a particular preferred embodiment, an electrochemical cell as defined above is provided in which the solid-state material according to the first aspect defined above, respectively obtainable by a method according to the second aspect defined above, may be in direct contact with lithium metal.

[0094] The electrochemical cell defined above comprises the following components: α) at ​​least one anode, β) at least one cathode; γ) at least one separator; wherein at least one of said three components is a solid structure selected from the group consisting of a cathode, an anode and a separator comprising a solid material according to the first aspect defined above, each obtained by the method according to the second aspect defined above.

[0095] Suitable electrochemically active cathode materials and suitable electrochemically active anode materials are known in the art. In the above-mentioned electrochemical cell, the anode α) may comprise graphitic carbon, metallic lithium or a metal alloy containing lithium as the anode active material. Due to its excellent electrochemical stability in direct contact with lithium metal, in certain preferred cases, in the solid structure defined above, the solid material according to the first aspect defined above, respectively obtained by the method according to the second aspect defined above, may be in direct contact with the anode containing lithium metal, so that no protective layer is required between them.

[0096] The electrochemical cells described above may be alkali metal-containing cells, in particular lithium-ion-containing cells. In lithium-ion-containing cells, charge transport is carried out by Li+ This is done by ions.

[0097] The electrochemical cell may have a disk-like or prismatic shape. The electrochemical cell may include a housing, which may be made of steel or aluminum.

[0098] A plurality of the above-mentioned electrochemical cells may be combined into an all-solid-state battery, which has both solid electrodes and solid electrolytes. A further aspect of the present disclosure relates to a battery, more particularly an alkali metal ion battery, in particular a lithium ion battery, which comprises at least one electrochemical cell as described above, for example two or more electrochemical cells as described above. The above-mentioned electrochemical cells can be connected to each other in the alkali metal ion battery, for example in series or parallel connection. A series connection is preferred.

[0099] The electrochemical cells, respectively batteries, described herein can be used to make or operate automobiles, computers, personal digital assistants, cell phones, watches, video cameras, digital cameras, thermometers, calculators, laptop BIOS, communication devices, or remote car locks, etc., as well as for stationary applications, such as energy storage devices in power plants. A further aspect of the present disclosure is a method for making or operating automobiles, computers, personal digital assistants, cell phones, watches, video cameras, digital cameras, thermometers, calculators, laptop BIOS, communication devices, remote car locks, etc., as well as for stationary applications, such as energy storage devices in power plants, by employing at least one inventive battery or at least one inventive electrochemical cell.

[0100] A further aspect of the present disclosure is the use of the electrochemical cell described above in an automobile, a bicycle operated by an electric motor, a robot, an aircraft (e.g., an unmanned aerial vehicle including a drone), a ship, or stationary energy storage.

[0101] The present disclosure further provides a device comprising at least one electrochemical cell of the present invention as described above.Preferably, the device is a mobile device such as a vehicle, for example, a car, a bicycle, an aircraft, or a water vehicle such as a boat or ship.Other examples of mobile devices are portable, for example, a computer, in particular a laptop, a telephone, or a power tool, for example, from the construction field, in particular a drill, a battery-powered screwdriver, or a battery-powered tacker.

[0102] The present invention will now be further illustrated by the following non-limiting examples. EXAMPLES

[0103] 1. Material Preparation Process a) For the preparation of comparative materials having the composition according to formula (I), precursors (each in powder form) (1) Li2S (2) Sb2S3 (3) LiI (4) Elemental sulfur (S) (5) optionally one of the elements Si, GeS2, and SnS2 were prepared by mixing precursors (1)-(4), or (1)-(5), respectively, according to the target stoichiometric ratio by grinding in a mortar under a protective gas atmosphere.

[0104] For the preparation of comparative materials, the precursors (each in powder form) (1) Li2S (2) P2S5 and optionally Sb2S3 (3) LiI (4) Elemental sulfur (S) (if the reaction mixture contains Sb2S3) A reaction mixture containing was prepared by mixing precursors (1)-(4) according to the target stoichiometric ratio in a mortar under a protective gas atmosphere. Steps b) and c) Each reaction mixture prepared in step a) was formed into pellets that were heat-treated in step b). For the heat treatment, each of the pelletized reaction mixtures was placed in a vitreous carbon crucible within a quartz tube sealed under vacuum.

[0105] Reaction mixtures in which the precursor (5) is Si were heat-treated at 500 °C for 7 days (0 < x < 0.5, where x has the same meaning as defined above for formula (I)) and at 550 °C for 7 days (0.5 ≤ x ≤ 0.7, where x has the same meaning as defined above for formula (I)).

[0106] Reaction mixtures in which the precursor (5) is GeS₂ were heat-treated at 550 °C for 20 hours in the first stage, then the temperature was shifted to 450 °C at a temperature change rate of 5 °C / min, and heat-treated at 450 °C for 100 hours in the second stage.

[0107] Reaction mixtures in which the precursor (5) is SnS₂ were heat-treated at 500 °C for 50 hours.

[0108] Reaction mixtures without the precursor (5) were heat-treated at 500 °C for 100 hours.

[0109] In each case, the reaction mixture was heated to the desired temperature using a heating rate of 5 °C per minute.

[0110] When the above-specified heat treatment period of step b) was completed, the formed reaction product was cooled to room temperature at a temperature change rate of 5 °C / min (step c)). In this way, solid materials having a composition according to general formula (I) were obtained respectively. Step d) Some of the solid materials with M = Si obtained in step c) (details are as follows) were pulverized, each was formed into pellets, and annealing in step d) was carried out.

[0111] The material was annealed at 500 °C for 7 days. In each case, the material was heated to the desired temperature using a heating rate of 5 °C per minute.

[0112] For details of the composition of the resulting materials, see Table 1 below.

[0113] The resulting material was in the form of pellets or chunks, which were then ground into powder for further processing.

[0114] 2. Ionic Conductivity Ionic conductivity was measured by electrochemical impedance spectroscopy (EIS). Typically, 150-200 mg of material powder was placed between two stainless steel rods and pressed into a 10 mm diameter pellet in a 3 metric ton hydraulic press for 3 min in an argon-filled glove box. EIS experiments were performed with a VMP3 potentiostat / galvanostat (Bio-Logic) at an amplitude of 100 mV within the frequency range of 1 MHz-10 mHz.

[0115] The lithium ion conductivities measured at 25° C. for all samples are shown in Table 1 below.

[0116] The composition is Li6PS5I, Li6Sb 0.1 P 0.9 S5I, Li6Sb 0.3 P 0.7 S5I, Li6Sb 0.5 P 0.5 S5I, Li6Sb 0.8 P 0.2The S5I material is a comparative material. Interestingly, partial substitution of phosphorus by antimony leads to a decrease in ionic conductivity when the Sb:P molar ratio is below 1:1. Indeed, this finding actually refutes the substitution of phosphorus by antimony. Surprisingly, a further increase in the Sb:P molar ratio reverses this trend, and the complete substitution of P by Sb (composition Li6SbS5I) increases the ionic conductivity by almost an order of magnitude compared to the material with composition Li6PS5I. Partial substitution of Sb by Si, Ge or Sn further increases the ionic conductivity, with Si having the greatest effect and Sn the least. Moreover, as is evident from Table 1, the annealing treatment (step d) described above) increases the ionic conductivity compared to the corresponding material with the same composition prepared without the annealing step d).

[0117] [Table 1]

[0118] 3. Stability against lithium Li 6.7 S 0.7 Sb 0.3 80 mg of S5I powder was packed into a poly(ether ether ketone) cylinder and cold pressed at 3 metric tons for 1 min to obtain a pellet with a diameter of 10 mm. A 10 mm diameter Li foil (99.9%, Sigma-Aldrich) was attached to both sides of the pellet to obtain the solid-state Li|Li 6.7 S 0.7 Sb 0.3 A symmetric cell of S5I|Li was obtained. The cell was then pressurized at a constant uniaxial pressure with a torque of 4 Nm using a stainless steel framework screw.

[0119] Solid electrolyte Li 6.7 S 0.7 Sb 0.3 To evaluate the stability of S5I, solid-state Li|Li 6.7 S 0.7 Sb 0.3 S5I|Li symmetric cells were tested at different currents and capacities (0.3 mA / cm2 and 0.3mAh / cm 2 0.6mA / cm for 600 hours; 2 , 0.6mAh / cm 2 The battery was then cycled at 1000 V for an additional 430 h. As can be seen from FIG. 1, a substantially stable voltage profile was obtained, indicating the electrochemical stability of the studied solid electrolyte in direct contact with lithium metal for a sustained period of at least about 1,000 h under the conditions of stripping and plating in a symmetric cell as described above.

[0120] 4.Structural analysis Powder X-ray diffraction (XRD) measurements were performed at room temperature using a PANalytical Empyrean diffractometer with Cu-Kα radiation equipped with a PIXcel area detector. XRD patterns for phase identification were obtained in Debye-Scherrer geometry with samples sealed in 0.3 mm glass capillary tubes under argon.

[0121] The XRD patterns of several solid materials having compositions according to formula (I) with M=Si, Ge or Sn, respectively, are shown in Figures 2a and 2b, in each case indexed to the cubic space group F-43m, which is the space group adopted by most other argyrogenites.

[0122] The XRD pattern in Figure 2a shows that the solid material having a composition according to formula (I) with M = Si is a polycrystalline powder, with very small proportions of LiI and Li2S present besides the material having a composition according to formula (I). Increasing the amount of Si (parameter x) increases the proportion of the secondary phases (mainly coming from the precursors LiI and Li2S).

[0123] In the XRD pattern of a solid material with M=Si, Si 4+ With increasing Sb content, the peak of argyrogenite shifts to smaller d-spacings (the distance between crystal planes) (see the close-up in Fig. 2a). This is because the Sb 5+ Si is smaller 4+ This indicates that the ions were successfully replaced.

[0124] The XRD patterns in FIG. 2b show that the material having the composition according to formula (I) where M=Ge is a polycrystalline powder with high phase purity, while the material having the composition according to formula (I) where M=Sn has traces of unknown impurities and LiI in the XRD pattern.

Claims

1. General formula (I), Li 7+x-y M x Sb 1-x S 6-y X y (I) (In the formula, M is one or more selected from the group consisting of Si, Ge, and Sn; When M is Si, 0.05≦x≦0.8; When M is Ge, 0.05≦x≦0.5; When M is Sn, 0.05≦x≦0.3; X is one or more selected from the group consisting of Cl, Br, and I; 0.05≦y≦2) and having a crystalline phase having the arginine germanite structure.

2. 2. The solid state material of claim 1, wherein 0.5≦y≦1.

5.

3. M is Si; 3. The solid state material of claim 2, wherein 0.2≦x≦0.

7.

4. M is Ge; 3. The solid state material of claim 2, wherein 0.2≦x≦0.

4.

5. M is Sn; 3. The solid state material of claim 2, wherein 0.15≦x≦0.

25.

6. The solid material according to any one of claims 3 to 5, wherein 0.8≦y≦1.

2.

7. The solid material according to any one of claims 1 to 6, wherein X is I.

8. A method for preparing a solid material as defined in any one of claims 1 to 7, said method comprising the following method steps: a) Precursors of: (1) Li 2 S (2) Sb 2 S 3 and one or both of the element Sb (3) one or more compounds LiX, where X is selected from the group consisting of Cl, Br and I (4) Element S (5) Optionally, one or more species selected from the group consisting of elemental forms of M and sulfides of M, where M, in each instance, is selected from the group consisting of Si, Ge, and Sn. wherein in said reaction mixture the molar ratios of the elements Li, M, Sb, S and X correspond to general formula (I); b) heat treating the reaction mixture at a temperature range of 400° C. to 600° C. for a total duration of 40 to 200 hours to form a reaction product; c) cooling the reaction product obtained in step b) so as to obtain a solid material having a composition according to general formula (I); A method comprising:

9. The following process d) annealing the solid material obtained in step c) at a temperature ranging from 400° C. to 600° C. for a duration of 40 to 200 hours; The method of claim 8 further comprising:

10. The precursor is (1) Li 2 S, (2) Sb 2 S 3 、(3)LiI、(4)Element S and (5) Element Si, element Ge, element Sn, SiS 2 , GeS 2 , and SnS 2 Either one of The method according to claim 8 or 9,

11. Use of a solid material according to any one of claims 1 to 7 as a solid electrolyte for an electrochemical cell.

12. A solid-state structure for an electrochemical cell, said solid-state structure being selected from the group consisting of a cathode, an anode and a separator, said solid-state structure for an electrochemical cell comprising a solid-state material according to any one of claims 1 to 7.

13. 8. An electrochemical cell comprising a solid-state material according to any one of claims 1 to 7.

14. 14. An electrochemical cell according to claim 13, wherein the solid material is a component of a solid structure as defined in claim 12.

Citation Information

Patent Citations

  • Lithium argyrodite

    US8075865B2